(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The study of physics requires the definition of general characteristics such as the so-called fundamental properties of space and time, which are homogeneity and isotropy. From the application of the homogeneity of time in the integral equations of the movement arises the theorem of the conservation of energy. That the parameter of variation be time leads to defining energy as scalar. Relativistic mechanics has shown that time is one of the dimensions of a tetra-dimensional space and, therefore, an event is projected in the spatial and temporal dimensions, this projection varies according to the reference system that is used. This indicates that equating time to a dimension of space, should be analyzed not only under the condition of homogeneity but also of the isotropy. This leads to analyzing energy as a vector. In classical mechanics, a body moving in a gravitational field its energy can be decomposed in two directions, one that remains constant, normal to the field, and the other that varies with gravity. This shows vector properties of energy. This study proposes a more general response through the energy field.